Pengaruh Budgetary, Participation, Information Asymmetry, Organizational Citizenship Behavior, Job Relevant Information terhadap kinerja di era VUCA - Hantono Hantono (Politeknik Ganesha Medan, 2022)
This research is intended to find out the variables Budgetary Participation (X1), Information Asymmetry (X2), Organizational Citizenship Behavior (X3), Job Relevant Information (X4) affects performance. The sample in this study was staff, employees who worked at the company in Medan City. In this study, it used a saturated sample of 76 people. The approach used is quantitative by processing data obtained from questionnaires after it is first converted into numerical data using the Likert scale. Data analyzed using multiple regression analysis, research instrument test consists of validity and realibility. The classic assumption test consists of a normality test, a heteroskedasticity test, a multicollinearity test, and an autocorrelation test. Hypothesis testing consists of the f test (simultaneous test), t test (partial test) and determinant coefficient test (R2) and the results show that relevant information, organizational citizenship behavior (OCB) has a significant effect on performance by proving a significance value below 0.05, while the budget participation variable, Information asymmetry, organizational citizenship behavior (OCB) has no significant effect on performance as evidenced by significance values above 0.05. The results of the determination test of 34.6% performance can be explained by variables Budgetary Participation (X1), Information Asymmetry (X2), Organizational Citizenship Behavior (X3), Job Relevant Information (X4) While 65.4% of performance variables can be explained by factors or other variables that have not been done in this study such as tax management, profitability. VUCA indirectly creates a new trend that is important for today's practitioners and company leaders to understand.